How Far Can I Go? Video Project-Based Learning as a Meaning-Making Process to Promote Students’ Speaking Proficiency - Teguh Sulistyo; Rizky Lutviana (Universitas Hamzanwadi, 2023)
Effective learning activities in the classroom that motivate students toward language proficiency should be thoughtfully implemented. One notable method is task-technology fit (TTF), which combines task-based language learning (TBLL) and project-based learning (PjBL). This study explores this intersection through video project-based learning (VPBL). It seeks to understand how VPBL interventions influence students' speaking proficiency, especially in areas of complexity, accuracy, and fluency, while also examining the role of students' self-efficacy and self-reflection. Utilizing a pre-experimental design without a control group, this research was conducted among second-year students of the English Education Program at Universitas PGRI Kanjuruhan Malang in their Speaking course. 37 students participated in a speaking test prompt and answered self-reflection and self-efficacy questionnaires, while 8 students underwent a more detailed interview regarding their VPBL experience. Results showed a general enhancement in speaking proficiency, primarily due to VPBL's unique structure and the student's capacity for self-reflection. Although improvements in fluency and accuracy were noted, there was not significant progress in complexity, indicating that while students utilized VPBL for refining their speaking skills, further efforts are required to advance their linguistic intricacy.